Evaluación de la Condición Corporal en Alpacas con el Reconstituyente General + Complejo Energético (hematol atp) en el CEASA. - Anchatuña Tipán, Paulina Nataly (2018)
This investigation was done in the Agricultural Sciences and Natural Resources Faculty of the Technical University of Cotopaxi whose objective is to evaluate the General Reconstitute (ATP) by weighing and body condition into alpacas, ten alpacas were selected for the treatment administration and data collection randomly separating in doses 1 (5 ml) and doses 2 (10 ml) applying three days in a row. To get the Hemodynamic Biometry results, the researcher collected blood samples using the vein puncture in the femoral vein with the amount of 5 ml to 10 ml of blood in a pipette vacutainer with lilac cap, and they were sent to the laboratory to achieve results for each animal. At the end of the general reconstitute application, the following results were obtained: in dose 1 with weight gain an average of 10 kg and body condition an average of 2,3. The Hemodynamic Biometry in the red series before the application had low analogous results in erythrocytes and increased hemoglobin, hematocrit, C.H.C.M. defining the presence of a macrocytosis. Red series at doses 2 before treatment shows a slight increase observed in Neutrophils with an L.S. of 27 – 15 x10^3/uL being a typical value of (2.6 – 27.0 x10^3/uL); it was defined with the presence of Neutrophilia, a bacterial infections, mycosis or parasitosis, allergic reactions, but this is controlled by the treatment having a value below 16.76x10^3/uL. The General Reconstitute obtained positive results in the monthly increase weigh and variation in the body condition in alpacas at CEASA.